(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Doppler ultrasound, also known as color ultrasound, is the leading ultrasound technique widely used today. Doppler ultrasound technology uses continuous waves to detect the direction and velocity of flow in the body. Therefore, fetal Doppler ultrasound in obstetrics has the effect of measuring the flow of blood vessels, examining the fetal heart and some functions that other fetal ultrasound techniques cannot perform. Specifically, Doppler ultrasound also helps measure the impedance index of the umbilical artery, middle cerebral artery in the fetus.